Streptomyces tirandamycinicus sp. nov., a Novel Marine Sponge-Derived Actinobacterium With Antibacterial Potential Against Streptococcus agalactiae - Huang, Xiaolong; Kong, Fandong; Zhou, Shuangqing; Huang, Dongyi; Zheng, Jiping; Zhu, Weiming (Frontiers in Microbiology, 2019)
A novel actinobacterium, strain HNM0039T, was isolated from a marine sponge sample collected at the coast of Wenchang, Hainan, China and its polyphasic taxonomy was studied. The isolate had morphological and chemical characteristics consistent with the genus Streptomyces. Based on the 16S rRNA gene sequence analysis, strain HNM0039T was closely related to Streptomyces wuyuanensis CGMCC 4.7042T (99.38%) and Streptomyces spongiicola HNM0071T (99.05%). The organism formed a well-delineated subclade with S. wuyuanensis CGMCC 4.7042T and S. spongiicola HNM0071T in the Streptomyces 16S rRNA gene tree. Multi-locus sequence analysis (MLSA) based on five house-keeping gene alleles (atpD, gyrB, rpoB, recA, trpB) further confirmed their relationship. DNA–DNA relatedness between strain HNM0039T and its closest type strains, namely S. wuyuanensis CGMCC 4.7042T and S. spongiicola HNM0071T, were 46.5% and 45.1%, respectively. The average nucleotide identity (ANI) between strain HNM0039T and its two neighbor strains were 89.65 and 91.44 %, respectively. The complete genome size of strain HNM0039T was 7.2 Mbp, comprising 6226 predicted genes with DNA G+C content of 72.46 mol%. Thirty-one putative secondary metabolite biosynthetic gene clusters were also predicted in the genome of strain HNM0039T. Among them, the tirandamycin biosynthetic gene cluster has been characterized completely. The crude extract of strain HNM0039T exhibited potent antibacterial activity against Streptococcus agalactiae in Nile tilapia. And tirandamycins A and B were further identified as the active components with MIC values of 2.52 and 2.55 μg/ml, respectively. Based on genotypic and phenotypic characteristics, it is concluded that strain HNM0039T represents a novel species of the genus Streptomyces whose name was proposed as Streptomyces tirandamycinicus sp. nov.. The type strain is HNM0039 T (=CCTCC AA 2018045 T = KCTC 49236 T).